Effects of Crossword-Picture Puzzle and Enhanced Explicit Teaching Strategies on Students’ Learning Outcomes in Basic Science in Southwestern Nigeria (2014)
Public examination records have shown that students record low achievement in basic science. This has been attributed to over dependence on the conventional method of talk and chalk. Scholars have thus recommended the use of other instructional strategies that could help students learn collaboratively and acquire problem solving skills. Two of such strategies are Crossword-Picture Puzzle and Enhanced Explicit Teaching strategies. There is paucity of research on their effects on students’ learning outcomes in basic science at the secondary school level in Southwestern Nigeria. This study, therefore, determined the effects of Crossword-Picture Puzzle (CPP) and Enhanced Explicit Teaching (EET) on students’ learning outcomes in basic science in Southwestern Nigeria while the moderating effects of gender and mental ability were also examined. The study adopted a pretest-posttest control group quasi-experimental design with 3x3x2 factorial matrix. Multi-stage sampling technique was used. Three hundred and eighty nine JSS 2 students from nine junior secondary schools were randomly selected in three states (Oyo, Ogun and Ondo). The schools were randomly assigned to experimental (CPP and EET) and control (CLM) groups, and the treatments were for 13 weeks. Seven instruments used were: Crossword-Picture Puzzle Teaching Strategy (r=0.76); Enhanced Explicit Teaching Strategy (r=0.72) and Conventional Lecture Method (r=0.74); Basic Science Students’ Achievement Test (r=0.70); Basic Science Students’ Attitude Scale (r=0.80); Australian Council for Educational Research Test (r=0.86) and Evaluation sheets for assessing research assistants. Seven hypotheses were tested at 0.05 level of significance. Data were analysed using ANCOVA and Scheffe post hoc test.There was significant main effect of treatment on students’ achievement score [F(2,389)=202.16; ᵑ2=.52]. Crossword-picture puzzle enhanced achievement scores (x=16.92) than EET (x=14.82) and CLM ( x =8.82). Treatment had significant main effect on students’ attitude to basic science [F (2,389) =11.51; ᵑ2=.06]. Crossword-picture puzzle enhanced attitude scores (x=58.43) than EET ( x =54.14) and CLM ( x =52.08). Gender had significant main effect on students’ achievement [F (1, 389) =3.99; ᵑ2=.01]. Male students had higher mean score of achievement in basic science ( x =13.85) than the female students ( x =13.19). Mental ability of students had significant main effect on their achievement [F (2, 389) =5.04; ᵑ2=.03]. High mental ability students had the highest mean score ( x =14.15) followed by moderate mental ability students ( x =13.44) and the low mental ability students ( x =12.96) respectively.Crossword-picture puzzle and enhanced explicit teaching strategies improved students’ academic achievement in and attitudes to basic science. Basic science teachers and curriculum developers should adopt the two activity based strategies for the improvement of students’ learning outcomes in basic science.